2016
DOI: 10.1016/j.nicl.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

A hierarchy of event-related potential markers of auditory processing in disorders of consciousness

Abstract: Functional neuroimaging of covert perceptual and cognitive processes can inform the diagnoses and prognoses of patients with disorders of consciousness, such as the vegetative and minimally conscious states (VS;MCS). Here we report an event-related potential (ERP) paradigm for detecting a hierarchy of auditory processes in a group of healthy individuals and patients with disorders of consciousness. Simple cortical responses to sounds were observed in all 16 patients; 7/16 (44%) patients exhibited markers of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 52 publications
1
52
0
Order By: Relevance
“…Applying this model to speech comprehension, Rohaut et al (2015) proposed a two-stage ERP profile, with an initial unconscious semantic prediction error in response to each word (the N400, typically onsetting around 200ms post-stimulus) and a late positive complex (LPC; in this case onsetting around 600ms post-stimulus) reflecting the ignition of meaning into conscious access. In support of this proposal, the N400 ERP has been observed in states of relative unawareness such as sleep, coma, and vegetative state (or unresponsive wakefulness syndrome) (Beukema et al, 2016;Ibáñez et al, 2006;Kotchoubey et al, 2005;Rämä et al, 2010) while the LPC has only been reported in conscious individuals, or in those who were conscious of and subsequently could report target words (Rohaut et al, 2015;Sergent et al, 2005;van Gaal et al, 2014).…”
Section: Introductionmentioning
confidence: 86%
“…Applying this model to speech comprehension, Rohaut et al (2015) proposed a two-stage ERP profile, with an initial unconscious semantic prediction error in response to each word (the N400, typically onsetting around 200ms post-stimulus) and a late positive complex (LPC; in this case onsetting around 600ms post-stimulus) reflecting the ignition of meaning into conscious access. In support of this proposal, the N400 ERP has been observed in states of relative unawareness such as sleep, coma, and vegetative state (or unresponsive wakefulness syndrome) (Beukema et al, 2016;Ibáñez et al, 2006;Kotchoubey et al, 2005;Rämä et al, 2010) while the LPC has only been reported in conscious individuals, or in those who were conscious of and subsequently could report target words (Rohaut et al, 2015;Sergent et al, 2005;van Gaal et al, 2014).…”
Section: Introductionmentioning
confidence: 86%
“…Attempts to discriminate auditory attention and processing in these MCS patients with electroencephalography (EEG) have focused on event‐related potential paradigms utilizing single words and repeated sound sequences 9, 10, 11, 12, 13. While such EEG measures appear to index cognitive processes, it is not clear that ERPs capture the type of auditory attention required to comprehend speech in everyday environments.…”
Section: Introductionmentioning
confidence: 99%
“…As we hypothesise that the neural representations of motor and non-motor verbs are not entirely overlapping, we also tested for differences in the scalp topographies across conditions with a randomisation test of global dissimilarity (see 51 ). For each time-window of interest, we calculated the global dissimilarity (i.e.…”
Section: Sensor Analyses: Erpsmentioning
confidence: 99%